Analisis Pengaruh Likuiditas terhadap Laba Bersih pada Sub Sektor Industri Semen di Bursa Efek Indonesia (BEI) Periode 2013-2017 - Sumiyati Sumiyati (Science of Management and Students Research Journal (SMS), 2019)
This study aims to analyze whether Current Ratio, Cash Ratio, Quick Ratio, and Working Capital To Total Asset Ratio have a significant or partial effect on Net Income in the Cement Industry sub-sector on the Indonesia stock exchange for the period 2013-2017. This research uses quantitative descriptive analysis method and qualitative descriptive analysis. The analytical tool of this research is the same as the analytical method, namely multiple linear regression using log. The results of the study show that simultaneously from this study shows the influence of Current Ratio, Cash Ratio, Quick Ratio, and Working Capital To Total Asset Ratio on Net Profit in the Cement Industry sub-sector on the Indonesia Stock Exchange for the period 2013-2017. Simultaneously with the number of Fitung Current Ratio, Cash Ratio, Quick Ratio and Working Caopital To Total Assets Ratio affect the Net Profit in the Cement Industry sub sector listed on the Indonesia Stock Exchange for the period 2013-2017. This is indicated by tcount greater than ttebel (6.469> 3.06) and by comparing the magnitude of the significant level of 0.05, then 0.001> 0.05 means that there can be an Analisis Pengaruh Likuiditas Terhadap Laba Bersih. influence between the variables Current Ratio, Cash Ratio, Quick Ratio and Working Capital To TotalAssets Ratio to Net Profit in the Cement Industry sub sector listed on the Indonesia Stock Exchange for the period 2013-2017. From the results of the examiners partially, it can be seen that the Current Ratio does not significantly affect Net Profit in the Cement Industry sub-sector listed on the Indonesia Stock Exchange for the 2013-2017 period. This right is indicated by the value of t count> t table (1,034 <2,131). Cash Ratio, does not significantly affect Net Profit in the Cement Industry sub sector listed on the Indonesia Stock Exchange for the 2013-2017 period. This right is indicated by the value of tcount> t table (1,633 <2,131). Quick Ratio, does not significantly affect Net Profit in the Cement Industry sub sector listed on the Indonesia Stock Exchange for the 2013-2017 period. This right is indicated by the value of tcount> t table (0.372 <2.131). From the results of the partial testers, it can be seen that the Working Capital To Total Assets Ratio, does not significantly affect Net Income in the Cement Industry sub sector listed on the Indonesia Stock Exchange for the 2013-2017 period.